2020
DOI: 10.1038/s41598-020-72194-1
|View full text |Cite
|
Sign up to set email alerts
|

Mitogenomic architecture of the multivalent endemic black clam (Villorita cyprinoides) and its phylogenetic implications

Abstract: The Indian black clam Villorita cyprinoides (Family: Cyrenidae), an extractive commercially exploited species with aquaculture importance contributing more than 70% of clam fishery in India, is endemic to the Indian peninsula. Currently, there is very sparse information, especially on the molecular data of Villorita. The present study aims to provide a comprehensive knowledge of mitogenome architecture and assess the phylogenetic status of Cyrenidae. This has resulted in reporting the first complete mitogenome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The monophyly of the superfamily Cyrenoidea including the freshwater-brackish water families Cyrenoididae, Cyrenidae and Glauconomidae in Imparidentia has been confirmed(Taylor et al 2009;Sharma et al 2012;Bieler et al 2014;Combosch et al 2017). Subsequent studies(Rahuman et al 2020;Crouch et al 2021) further confirmed the close relationship of three families in Cyrenoidea as (Cyrenidae + (Cyrenoididae + Glauconomidae)). More recently, the transcriptomic study conducted byLemer et al (2019) included representatives from Cyrenidae (Corbicula f luminea (O. F. Müller, 1774) and Polymesoda caroliniana (Bosc, 1801)), Glauconomidae (Glauconome rugosa Hanley, 1843) and Cyrenoididae (Cyrenoida floridana).…”
mentioning
confidence: 81%
“…The monophyly of the superfamily Cyrenoidea including the freshwater-brackish water families Cyrenoididae, Cyrenidae and Glauconomidae in Imparidentia has been confirmed(Taylor et al 2009;Sharma et al 2012;Bieler et al 2014;Combosch et al 2017). Subsequent studies(Rahuman et al 2020;Crouch et al 2021) further confirmed the close relationship of three families in Cyrenoidea as (Cyrenidae + (Cyrenoididae + Glauconomidae)). More recently, the transcriptomic study conducted byLemer et al (2019) included representatives from Cyrenidae (Corbicula f luminea (O. F. Müller, 1774) and Polymesoda caroliniana (Bosc, 1801)), Glauconomidae (Glauconome rugosa Hanley, 1843) and Cyrenoididae (Cyrenoida floridana).…”
mentioning
confidence: 81%
“…The healthy adult black clam specimens with a shell length (SL) of 30 ± 3.5 mm and a total body weight (BW) of 35–40 grams were collected using kolli (an indigenous hand rake net) from Vembanad Lake, a Ramsar site in Kerala, India in March 2021. The study locations in Vembanad Lake included the southern dominant freshwater region, Muhamma: 9°36′18.6″N 76°22′01.2″E and the northern saltwater region, Vaikom: 9°44′35.8″N 76°23′03.4″E, divided seasonally by the Thaneermukkom barrage 10 . Individuals were primarily identified using malacological literature 26 .…”
Section: Methodsmentioning
confidence: 99%
“…Popularly known as the Indian black clam, Villorita cyprinoides is an endemic cyrenid clam inhabiting the estuaries of Peninsular India. Being a readily available and affordable protein source, this artisanal fishery accounts for more than 70 percent of the Indian clam fishery, making it economically valuable and overutilized 10 . However, the wild population of the clam faces significant challenges including multiple climatic stressors and anthropogenic pressures such as overfishing and habitat destruction.…”
Section: Background and Summarymentioning
confidence: 99%